Popular music, digital technologies and data analysis: New methods and questions. (April 2019) - Hamilton, Craig
This article explores how respondents to The Harkive Project (www.harkive.org ) are enfolding streaming services and automated recommendation systems into their everyday music reception practices. Harkive is an online project running annually on a single day in July that invites people to provide detail and reflection on their experiences with music. Since the project first ran in 2013, it has gathered over 10, 000 individual entries. It is conceived as an ongoing experiment in research methodology that attempts to produce an online social space that encourages reflection from respondents about the detail of their music reception practice, while simultaneously acting as a place able to replicate commercial practices around data collection and analysis. This article will demonstrate how such a research process can produce rich descriptive data from respondents who provide a useful snapshot of contemporary music reception practice. The article begins with an overview of how streaming services, data collection from numerous online channels and automated recommendation systems interrelate, and how together they raise questions around how people engage in acts of music reception. It then describes how Harkive is based on similar types of computational/algorithmic processing to those used by key players in the digital music space. The analysis that follows shows that although respondents are engaging in everyday use of streaming services and dynamic recommendations, this engagement tends to be spread across a variety of online channels used in differing combinations, and that it is often recommendations from 'traditional' routes, such as media outlets (newspapers, radio stations) and users' own social groups, that feature prominently in respondent descriptions. Indeed, what Nowak (2016) calls the 'affective' element of recommendation appears to be rooted in existing practices that are still in the process of being transposed to the relatively recently emerged digital platforms, rather than – and sometimes in spite of – the rhetorical framing of those platforms as key sites for recommendation and discovery by the companies who operate them. Through a discussion of those findings, and based on an update of Michael Bull's concept of 'auditory nostalgia' (2009), it is then suggested that examining how listeners are enfolding the new technologies of music reception into their everyday routines and routes to meaning-making may be a useful direction for future research. The article then suggests that a mode of working where scholars attempt to reflexively harness data-derived processes may be useful in producing that work, and that experimental and practice-led approaches could enable popular music scholars and listeners alike to develop better epistemic responses to the data-related technologies that have recently helped bring about such huge changes in our everyday music reception practice.